2020
DOI: 10.1177/0967033520939319
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of critical nitrogen contents in peach orchards using visible-near infrared spectral mixture analysis

Abstract: The aim of this study was to predict the critical nitrogen (N) content in peach trees using spectrometric measurements. A nutrient-controlled hydroponics experiment was designed for this purpose. Peach saplings were grown under three N conditions: deficient, sufficient, and excessive. The reflectance values of a plant leaves were measured using a handheld field spectroradiometer fitted with a plant probe. The N contents of leaves were determined in the laboratory and Gaussian mixture discriminant analysis (GMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Despite that, encouraging results have been obtained with reflectance spectra. For peach tree, VIS-NIR reflectance spectra were used to classify leaves according to deficient (N < 2.99%), sufficient (N 3.00 to 3.50%), and excessive (N > 3.50%) nitrogen content [17]. Gaussian mixture discriminant analysis provided a spectral index combining values at 425 nm, 574 nm, 696 nm, and 700 nm that achieved a general correct classification rate of 75% under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, encouraging results have been obtained with reflectance spectra. For peach tree, VIS-NIR reflectance spectra were used to classify leaves according to deficient (N < 2.99%), sufficient (N 3.00 to 3.50%), and excessive (N > 3.50%) nitrogen content [17]. Gaussian mixture discriminant analysis provided a spectral index combining values at 425 nm, 574 nm, 696 nm, and 700 nm that achieved a general correct classification rate of 75% under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the data containing spectrometric measurements of the critical nitrogen nutrient content of peach leaves were provided from the literature [10]. The data includes training (𝑁 1 = 84) and test (𝑁 2 = 96) data with 𝐾 = 3 class and 𝑃 = 601 variables.…”
Section: A the Real Datasetsmentioning
confidence: 99%
“…One of the important problems with these methods is to select multiple features carrying the same information when strong correlations exist between features unnecessarily. For example, high-dimensional and strongly correlated data such as reflectance, image, text or DNA microarray data problem arises that hindering the learning process, especially in classification [6,[8][9][10][11]. The focus of this study is to determine the variables that will give the highest classification accuracy in classification of high dimensional data.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that NIR spectroscopy has high accuracy in predicting essential elements (N, P, K, Ca, Mg, and S 0.76 ≤ R 2 ≤ 0.98) and most trace elements (Fe, Mn, Cu, Mo, B, Cl, and Na 0.64 ≤ R 2 ≤ 0.81), and the application of NIR spectroscopy on fresh leaves is also quite accurate [15]. Dedeoglu et al [16] designed hydroponics experiments on peach trees treated with different contents of nitrogen and constructed nitrogen estimation models with reflectance at 425 nm, 574 nm, 696 nm, and 700 nm. The results showed that the models developed using hyperspectral reflectance could distinguish different nitrogen nutrient states of plants with an accuracy of ≥70%.…”
Section: Introductionmentioning
confidence: 96%